2009
DOI: 10.1038/ismej.2008.127
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of soil acidobacterial diversity using pyrosequencing and clone library analyses

Abstract: Acidobacteria are ubiquitous and abundant members of soil bacterial communities. However, an ecological understanding of this important phylum has remained elusive because its members have been difficult to culture and few molecular investigations have focused exclusively on this group. We generated an unprecedented number of acidobacterial DNA sequence data using pyrosequencing and clone libraries (39 707 and 1787 sequences, respectively) to characterize the relative abundance, diversity and composition of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
578
15
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 1,013 publications
(690 citation statements)
references
References 60 publications
82
578
15
15
Order By: Relevance
“…Several members of this phylum have been evidenced to be facultative or obligatory anaerobic organotrophs (Jones et al, 2009;Fierer et al, 2007). Hence, their abundance may be particularly favored by high soil moisture together with effects on community structure, as we found in the present field study and was proven by other reports (for example, Janssen, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…Several members of this phylum have been evidenced to be facultative or obligatory anaerobic organotrophs (Jones et al, 2009;Fierer et al, 2007). Hence, their abundance may be particularly favored by high soil moisture together with effects on community structure, as we found in the present field study and was proven by other reports (for example, Janssen, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…PCA at all levels demonstrated that the large gap between CV and the other regions in the unpolluted area was in accordance with the fact that the predominance of Acidobacteria in CV was closely related with the strong acidic nature of the site. Many research studies have confirmed that this phenomenon had close relationship with the strong acidic nature of soil (Jones et al 2009). …”
Section: Correlation Between Community Structure and Environmental Famentioning
confidence: 87%
“…With this level of coverage, the full extent of microbial diversity has not been surveyed; however, previous work (Fierer et al, 2008;Jones et al, 2009;Lauber et al, 2009;Miller et al, 2009) has shown that patterns of beta diversity and overall taxon relative abundances of dominant lineages can be accurately inferred with this depth of sequencing. Of these reads, 159 618 (99%) could be confidently identified, the majority to the level of family or genus.…”
Section: Resultsmentioning
confidence: 99%